Association between the use of insecticide-treated bed net and malaria infection in Ende District, East Nusa Tenggara - Maria Salestina Sekunda; Anak Agung Sagung Sawitri; Pande Putu Januraga (Public Health and Preventive Medicine Archive, 2017)
Background and purpose: Malaria is a public health problem in Eastern Indonesia, especially in East Nusa Tenggara. Insecticidetreated bed net was massively distributed in 2014, however the incidence of malaria in Ende District remains high. This study aims to examine association between the use of insecticide-treated bed net and malaria infection. Methods: A case control study was conducted in Wewaria Subdistrict, Ende District in 2016 involving 67 cases and 134 controls. Data on the use of insecticide-treated bed net which include methods of net use, net use practice, net maintenance and its current conditions were obtained through interviews and observations. Physical conditions of respondent’s house that include conditions of the wall, floor, window, ventilation, ceiling and lighting were also documented through observations. Data were analysed using logistic regression. Results: Case and control groups were comparable for gender (p=1), age (p=0.9), education level (p=0.9) and occupation (p=0.6). This study found that five variables were associated with malaria infection: irregular use of the insecticide-treated bed net (AOR=4.08; 95%CI: 1.87-8.89), torn net (AOR=2.23; 95%CI: 1.10-4.54), inadequate lighting (AOR=3.64; 95%CI: 1.77-7.47), humid floor (AOR=3.02; 95%CI: 1.24-7.34) and holes or broken ceiling (AOR=2.41; 95%CI: 1.02-5.72). Conclusions: The use of insecticide-treated bed net and physical conditions of the house are risk factors for malaria infection.